2022
DOI: 10.1002/wwp2.12084
|View full text |Cite
|
Sign up to set email alerts
|

Waterbody status of upper Ganga basin and its major tributaries using enviro‐assessment techniques

Abstract: In the past two decades, freshwater bodies and their water quality have deteriorated rapidly due to several natural and anthropogenic causes, as well as rapid urbanization and industrialization. Using environmental assessment tools, eight sampling stations were used to assess the water quality of the upper Ganga and its major headstreams between January 2019 and December 2021 and to assess the impact of human-led activities on the environment and the suitability of the catchment basin to perpetuate aquatic eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These aims may be reflected in various policies and initiatives implemented by the central government, state governments, and other relevant agencies to achieve sustainable water management and address the water‐related challenges faced by India. It's important to note that the specific aims and priorities may evolve over time to adapt to changing circumstances and emerging water issues in the country (Malik et al, 2020b, 2022; Sharma et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These aims may be reflected in various policies and initiatives implemented by the central government, state governments, and other relevant agencies to achieve sustainable water management and address the water‐related challenges faced by India. It's important to note that the specific aims and priorities may evolve over time to adapt to changing circumstances and emerging water issues in the country (Malik et al, 2020b, 2022; Sharma et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The recorded value of DO was within the acceptable limit by FMEnv (2011), that is, >6 mg/L. Sharma, Malik, et al (2022) reported that the value of DO ranges from 7.20 to 8.69 mg/L in the upper Ganga river basin, which is slightly higher than our sampling rivulets. According to Sharma, Sharma, et al (2022), several factors can reduce oxygen levels in water, such as nutrient levels, fluctuations in water flow, increases in water temperatures, and the buildup of several chemicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it serves the UNESCO World Water Quality Portal, a cutting-edge instrument for monitoring water quality via satellite Ground Observation, in watersheds of the globe. According to India's National Water Policy (2012), the country is experiencing significant difficulties as a result of having to accommodate its rapid population increase while also contending with the global threat posed by climate change (Sharma et al, 2022).…”
Section: Conservation Strategies For the Growth And Development Of In...mentioning
confidence: 99%